2021
DOI: 10.1177/09603271211023789
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolic acid induces apoptosis and autophagy of endometrial carcinoma cells via inhibiting PI3K/Akt/mTOR pathway in vivo and in vitro

Abstract: Endometrial cancer (EC) is the fourth most common malignancy in women in developed countries. The prognosis of EC is extremely poor, and it is an important factor that contributes to the death of patients. Therefore, studying EC pathogenesis and therapeutic targets, and exploring effective drugs are the primary tasks to improve the prognosis of EC. In the present study, we aimed to explore the function of ginkgolic acid (GA) in EC cell apoptosis and autophagy through PI3K/Akt/mTOR signal pathway in vitro and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Furthermore, the PI3K/Akt/mTOR pathways are regarded as promising targets for cancer therapy due to their important role in the process of cell proliferation, growth, survival, and mobility [ 46 ]. Consequently, multiple candidate anticancer agents suppress tumor growth by inhibiting PI3K/Akt/mTOR pathways and then inducing autophagy, as well as apoptosis of cancer cells [ 47 , 48 ]. In line with these, Smp24 suppressed the phosphorylation of PI3K/Akt/mTOR and increased the autophagic flux of LC3A/B-II/I, as well as the degradation of p62 ( Figure 8 A,B).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the PI3K/Akt/mTOR pathways are regarded as promising targets for cancer therapy due to their important role in the process of cell proliferation, growth, survival, and mobility [ 46 ]. Consequently, multiple candidate anticancer agents suppress tumor growth by inhibiting PI3K/Akt/mTOR pathways and then inducing autophagy, as well as apoptosis of cancer cells [ 47 , 48 ]. In line with these, Smp24 suppressed the phosphorylation of PI3K/Akt/mTOR and increased the autophagic flux of LC3A/B-II/I, as well as the degradation of p62 ( Figure 8 A,B).…”
Section: Discussionmentioning
confidence: 99%
“…A multitude of research has shown that blocking the PI3K/AKT/mTOR pathway may lead to heightened cellular autophagy processes. Within the EC cell lines Ishikawa and HEC1-B, escalating levels of ginkgolic acid progressively suppressed the PI3K/AKT/mTOR pathway, boosting autophagy in cancerous cells, thus curtailing cell growth and triggering apoptosis ( 75 ). Inhibiting the PI3K/AKT/mTOR pathway in EC cell lines HEC-1A and Ishikawa led to increased autophagy activity and reduced cancer cell proliferation, migration, and invasion, achieved by inhibiting FAM83B, a Family 83 member with similar sequences.…”
Section: The Significance Of Autophagy In Resistance To Drugs In Endo...mentioning
confidence: 99%
“… 82 The PI3K/AKT pathway is a key regulator of survival during cell stress, and abnormal activation of this pathway is often observed in tumors. 13 , 83 , 84 , 85 A recent study showed that inhibiting TP53BP2 expression promotes the growth and migration of triple negative breast cancer (TNBC) cells through this pathway. 13 PI3KR1 (P85 α) negatively regulates the PI3K pathway.…”
Section: Suppression Of Cancer Signaling Pathways By Tp53bp2mentioning
confidence: 99%